2021
DOI: 10.1016/j.joim.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary fibrosis in one convalescent patient with corona virus disease 2019 by oral traditional Chinese medicine decoction: A case report

Abstract: After one-month of oral treatment with traditional Chinese medicine decoction, without using other drugs, the lung inflammatory exudate, pulmonary fibrosis and quality of life of a 61-year-old female patient with corona virus disease 2019 (COVID-19) were significantly improved. No recurrence or deterioration of the patient’s condition was found within seven weeks of treatment and follow-up, and no adverse events occurred, indicating that oral Chinese medicine decoction was able to improve the pulmonary inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…COVID-19 is a worldwide pandemic that has proliferated across the globe since its spread from Wuhan, China, in December 2019 [1][2][3]. Since then, full clinical presentations of this viral infection are still not fully understood, as being an RNA virus with many variants, its clinical manifestations are always different [4].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a worldwide pandemic that has proliferated across the globe since its spread from Wuhan, China, in December 2019 [1][2][3]. Since then, full clinical presentations of this viral infection are still not fully understood, as being an RNA virus with many variants, its clinical manifestations are always different [4].…”
Section: Introductionmentioning
confidence: 99%
“…Various symptoms were targeted in one publication ( Table 1 ) [ 26 ]. Among the two clinical studies, one was a prospective case-control study [ 10 ], and the other was a single case report [ 11 ]; both assessed the clinical effects of Chinese herbal medicine (CHM) decoctions for lung inflammation. In these two studies, CHM was reported to be effective in relieving symptoms of pulmonary dysfunction in patients after COVID-19 infection [ 10 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Wang et al [22] showed that the Lianhua Qingwen Capsule can significantly improve the effect of Western medicine in alleviating COVID-19 symptoms. Also, the consumption of Chinese herbal medicine as a co-therapy with acupuncture [23] , [24] was shown to be beneficial to COVID-19 treatment.…”
Section: Using Clinical Data To Verify the Effectiveness Of Cam Treatments For Covid-19mentioning
confidence: 99%